Ministry of Defence expenditures impact on economic growth of Ukraine - Коваль, Олесь (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . With the start of the second stage of the Russian-Ukrainian war, the Government of Ukraine and its military command faced an objective examination of the results of years of efforts to develop Ukraine's national security and defence sector. At the same time as defence capability was being enhanced, economic performance was on the rise. This led us to test the hypothesis of whether the increased defence capability caused this growth. This study aims to clarify the relationship between military expenditures and economic growth in Ukraine. The object of the study is a consistent and long-term process of economic growth of the state along with an increase in the level of defence capability as a result of military expenditures in the context of financial support from the Ministry of Defence of Ukraine. Methods. Theoretical methods: analysis, synthesis, abstraction, generalisation, induction, deduction, explanation, classification. Empirical methods: hypothesis, observation, experiment, description. Results. This paper defines "military capabilities" and their relationship with military potential. It has been established that the ability to use military potential (military power/strength) is a military capability. Military expenditures are used to develop capabilities in the Ministry of Defence of Ukraine's system. Thus, allocating and redistributing expenditures for the army's needs is financial support. The armed forces' financial support drives the country's economic growth. To establish this fact, the leading indicators of military expenditures in the Ministry of Defence of Ukraine (from now on – MoD) were analysed and the indicator of economic growth – gross domestic product (from now – GDP) from 2012 to 2021. This period is crucial for Ukraine's national security, defence, and economic growth, as the basic principles of state defence policy were established during this time. Thismotivated us to analyse financial and defence indicators to determine their interrelationship. C o n c l u s i o n s . Two variables were defined as military expenditures and the GDP, where the first variable is independent and the second is dependent. A high correlation between military spending and economic growth in Ukraine was found by constructing a scatter plot, performing the relevant calculations, obtaining the data in an ANOVA table, setting up a regression line, and conducting null hypothesis tests.
Keywords: military capabilities, military potential, military expenditures, GDP, economic growth, linear regression, correlation